Analisis Mekanisme Pembentukan Budaya Industri melalui Teaching Factory: Studi Kasus di SMKN 2 Surakarta - Valiant Lukad Perdana Sutrisno (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – Teaching Factory (TEFA) is widely promoted to align vocational schools with industry demands, yet many studies emphasize implementation factors rather than explaining how TEFA operationally institutionalizes industrial work culture in day-to-day school practices. This study examines the patterns and mechanisms through which industrial work culture is habituated in a TEFA-based vocational school.Methods – This qualitative case study (interpretive paradigm) was conducted at SMKN 2 Surakarta following Yin’s case study procedures. Data was generated through semi-structured in-depth interviews with six key informants (head of expertise program, workshop head, productive teachers, and students) and supported by relevant documents. Data were analyzed iteratively using open–axial–selective coding to construct categories and an integrative theme. Trustworthiness was strengthened through data and method triangulation, and participants’ consent and anonymization were ensured. Findings – The findings show that Teaching Factory (TEFA) functions as an institutional ecosystem for industrial culture formation, rather than merely a production-based learning model, as students internalize industrial values through authentic daily work practices. Industrial culture is formed through the integration of strategic orientation, including quality and market legitimacy, financial sustainability, policy alignment, and project-based production, and operational mechanisms, such as block scheduling, digital or fingerprint-based attendance, structured daily routines, and tiered task distribution. The study further indicates that TEFA’s effectiveness is context-dependent and relies on consistent implementation, as variations in resources, leadership, and operational discipline influence the strength of industrial culture habituation. Research Implications – The study offers conceptual insights into TEFA as a mechanism for institutionalizing industrial culture in vocational education.